Performance evaluation of Location-Sensitive Handoff using positioning method / Azuwa Ali and Saiful Fadzli Salian - Ali, Azuwa; Salian, Saiful Fadzli (2009)
Handoff is one of the most important processes in mobile communication system. Radio resource management planning effectiveness depends on the successfulness of handoff process in maintaining the connection. With the help of location information, handoff process can be optimize and increase the intelligent of radio resource management. This project investigate the performance of handoff process with the help of location information which is called Location-Sensitive Handoff (L-SH) using the location positioning method. Location positioning method chosen in L-SH is Observed-Time Difference of Arrival (OTDOA). Simulation model is developed and done using Matlab® in analyzing and comparing the performance of conventional handoff with L-SH. Handoff performance is analyze based on the number of handoff occurred with respect to user mobility, fading and propagation effect. Result from simulation shows that L-SH is more efficient as compare to conventional handoff and L-SH performance is less affected by fading and propagation. New algorithm is also proposed in order to enhance handoff process.